CULTURAL INSTITUTION IN UZBEKISTAN: THE HISTORY OF THE ESTABLISHMENT OF A RECREATION PARK (CASE STUDY OF FERGANA REGION) (World Bulletin of Management and Law, 2026)
This article describes the history of the emergence, development, and contemporary significance of the recreational park in the city of Fergana, which is recognized as an important cultural site.